Validation of Suitable Reference Genes for Quantitative Gene Expression Analysis in Panax ginseng - Wang, Meizhen; Lu, Shanfa (Frontiers in Plant Science, 2016)
Reverse transcription-qPCR (RT-qPCR) has become a popular method for gene expression studies. Its results require data normalization by housekeeping genes. No single gene is proved to be stably expressed under all experimental conditions. Therefore, systematic evaluation of reference genes is necessary. With the aim to identify optimum reference genes for RT-qPCR analysis of gene expression in different tissues of Panax ginseng and the seedlings grown under heat stress, we investigated the expression stability of eight candidate reference genes, including elongation factor 1-beta (EF1-β), elongation factor 1-gamma (EF1-γ), eukaryotic translation initiation factor 3G (IF3G), eukaryotic translation initiation factor 3B (IF3B), actin (ACT), actin11 (ACT11), glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and cyclophilin ABH-like protein (CYC), using four widely used computational programs: geNorm, Normfinder, BestKeeper, and the comparative ΔCt method. The results were then integrated using the web-based tool RefFinder. As a result, EF1-γ, IF3G and EF1-β were the three most stable genes in different tissues of P. ginseng, while IF3G, ACT11 and GAPDH were the top three-ranked genes in seedlings treated with heat. Using three better reference genes alone or in combination as internal control, we examined the expression profiles of MAR, a multiple function-associated mRNA-like non-coding RNA (mlncRNA) in P. ginseng. Taken together, we recommended EF1-γ/IF3G and IF3G/ACT11 as the suitable pair of reference genes for RT-qPCR analysis of gene expression in different tissues of P. ginseng and the seedlings grown under heat stress, respectively. The results serve as a foundation for future studies on P. ginseng functional genomics.